Management of black-grass (Alopecurus myosuroides Huds.) in winter wheat and taking into account the soil activity of post-emergence herbicides - Meiners, Ingo; Justus Liebig University Giessen (My University, 2015)
The emergence of black-grass (Alopecurus myosuroides) was observed over three growing seasons (2009-2012) on agricultural fields at different locations within Hessen (Rauischholzhausen, Gießen and Wicker) and Germany. The emergence pattern generally varied within years, locations and cultivation systems. At the experimental station Rauischholzhausen, under low tillage conditions, A. myosuroides emerged steadily between September and May in all years. Peak emergence of about 75-90% occurred after sowing until the middle of October, followed by continuous emergence until winter by 9-24% and another peak of 1-12% in the spring. Observations confirm that a prolonged emergence with late flushes of black-grass usually occur before winter and/or in the spring. It was concluded that herbicide treatments (pre- and post-emergence) would have to be more robust, containing active ingredients with a long lasting residual component in order to cover the protracted period of black-grass emergence, especially in years with a high dormancy level.

Der Ackerfuchsschwanz (Alopecurus myosuroides) stellt ein bedeutendes Schadgras in heutigen Getreide-Fruchtfolgen dar, dessen Bekämpfung durch eine zunehmende Resistenz gegen bestimmte Herbizidwirkstoffe erschwert ist. In den Jahren 2009 bis 2012 wurden daher mehrere Gefäß- und Parzellenversuchen mit Winterweizen durchgeführt, um das Keimungsverhalten von Ackerfuchsschwanz sowie die Wirkung von unterschiedlichen Herbizidstrategien und agronomischen Maßnahmen zur Bekämpfung von Ackerfuchsschwanz zu untersuchen.
Management von Ackerfuchsschwanz (Alopecurus myosuroides Huds.) in Winterweizen unter besonderer Berücksichtigung der Bodenwirkung von Nachauflauf-Herbiziden
Keywords: ddc:630